Machine Learning Based on Cloud Solutions - Chmielecki, Przemysław (Journal of Education, Technology and Computer Science, ISSN 2719-6550, e-ISSN 2719-7417, 2019)
Cognition is a domain of thinking creatures, isn’t it? Based on that computers cannot learn anything more than was in the initial data feed. In this article, I just want to defend that nowadays technical solutions can break this rule. The aim of this article is to provide a short technical overview what Machine Learning (ML), Artificial Intelligence (AI) and Neural Networks (NN) were before in the area of standalone gigantic servers, and how do they look now in Cloud Computing (CC) times. The ML paradigm is not any more reserved for big enterprises only but now is available for single internet user. I just want to present AWS and Azure, as the biggest CC providers, functionalities and potential usage of such Cognitive Services (CS) in current internet services. The great example is for instance bot usage instead of diving deep in the FAQ on the company website or digging into the corporate wiki. Another big area is graphics analysis and sound or text recognition. Those are only examples of predefined CC functions ready for use right now in the public cloud.